2012
DOI: 10.1089/met.2011.0112
|View full text |Cite
|
Sign up to set email alerts
|

Significant Increase in High-Density Lipoprotein Cholesterol with Fibrates Is Associated with Low Pretreatment High-Density Lipoprotein Cholesterol: Findings from an Outpatient Clinic Setting

Abstract: Our results may explain the discrepancies observed in some randomized controlled trials whereby subgroup analysis of patients with the metabolic syndrome appeared to show benefit whereas this was absent in the total cohort. Thus, future interventional studies using fibrates should perhaps focus on patients with low HDL-C levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 31 publications
(24 reference statements)
0
4
0
Order By: Relevance
“…Significant changes were seen in TC, TG and HDL-C following fibrate treatment. These findings were anticipated as our patient group was a subset of the cohort previously reported regards the above analytes (Ramachandran et al, 2012; Abbas et al, 2012). All three LFT studied decreased (Table 1) with fibrate treatment with paired t -Test showing the changes to be significant; GGT (p < 0.0001), ALT (p = 0.0014) and ALP (p < 0.0001).…”
Section: Resultsmentioning
confidence: 63%
“…Significant changes were seen in TC, TG and HDL-C following fibrate treatment. These findings were anticipated as our patient group was a subset of the cohort previously reported regards the above analytes (Ramachandran et al, 2012; Abbas et al, 2012). All three LFT studied decreased (Table 1) with fibrate treatment with paired t -Test showing the changes to be significant; GGT (p < 0.0001), ALT (p = 0.0014) and ALP (p < 0.0001).…”
Section: Resultsmentioning
confidence: 63%
“…In our opinion, many chronic pathologies are heterogeneous, with common phenotypes leading them to be grouped as single diseases . We have previously shown that statins and fibrates exert greater effects in certain dyslipidaemic subgroups . With HG heterogeneity in mind, we wished to identify subgroups where the previously observed associations were more marked.…”
Section: Discussionmentioning
confidence: 99%
“…1a), is used for hypercholesterolemia and hypertriglyceridemia to reduce morbidity and mortality associated with cardiovascular disease as a lipid regulating agent [1][2][3][4]. FF is absorbed from the gastrointestinal tract, and is principally hydrolysed by the CYP3A4 isozyme to its active and major metabolite fenofibric acid (FFA, Fig.…”
Section: Introductionmentioning
confidence: 99%